AN EXPLORATORY RESEARCH ON RURAL AREAS ACCORDING TO NUTS CLASSIFICATION, IN TWO NEIGHBORING COUNTRIES: ROMANIA AND BULGARIA - Valentin-Cosmin SĂRĂCIN; Ilona-Elena-Cristina ȚÎRCĂ; Lucian CONSTANTIN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This exploratory research is based on statistical data about some indicators for the context of rural development, from different countries of EU, but also it is a comparative study of speciality literature regarding sustainable development and rural development, in two neighbouring countries: Bulgaria and Romania. The research is based on a methodology that involves the use of statistical data on leading indicators for the rural development context, from two neighbouring countries, Romania and Bulgaria. By analysing economic indicators we found that in some countries there are large discrepancies between urban zones and rural zones. This discrepancy between rural zones and urban zones is confirmed by environmental indicators, which still have positive influences on other fields, in which there was a positive evolution. Both Romania and Bulgaria, the two countries used in this study benefit from varied tourism resources, both natural and anthropogenic, insufficiently developed and exploited. Through these they can develop rural areas, opting for the development and support of rural tourism, the diversification of the rural population, in order to create new non-agricultural activities as a result of exploitation of the agricultural sector, with implications for increasing the number of jobs and increasing of the employment rate among the rural population.